Implementation of the Policy on the Assessment System for Prisoner Development in the Ternate State Detention Home - Warang, Mukadam; Utami, Sawitri Budi; Nasution, Vivi Indra Amelia (Journal Research of Social Science, Economics, and Management, 2025)
This study examines the implementation of the Prisoner Development Assessment System (SPPN) at Ternate State Prison, guided by Ministerial Regulation No. 35/2018 and the Director General of Corrections’ Decree PAS-10.OT.02.02/2021, aimed at ensuring objective behavioral assessments and human rights protection. Using a qualitative approach and Edward III’s (1980) policy implementation theory, the research identifies key obstacles: ineffective communication, inadequate technical training, and weak supervision, which hinder optimal SPPN execution (Syahrul et al., 2020). Findings reveal that despite policy commitment, implementation remains conditional, with limited outreach and resource constraints exacerbating disparities compared to urban prisons like Tangerang (Shania Damayanti & Mulyani Rahayu, 2023). The study highlights the urgent need for structured training, digital tools, and cross-facility comparisons to enhance SPPN efficacy. Implications suggest that addressing these gaps could improve rehabilitation outcomes, reduce recidivism, and align correctional practices with national bureaucratic reform goals.